Low‐complexity BER computation for coherent detection of orthogonal signals - L. Rugini; G. Baruffa (Electronics Letters, 2021)
Abstract The bit error rate (BER) computation for coherently detected orthogonal signals in additive white Gaussian noise requires numerical integration, which can be cumbersome in low‐complexity devices. Here, a BER computation approach that circumvents the need for repeated numerical integration is proposed. First, a low‐complexity BER approximation formula is selected, with unknown parameters to be determined. Second, this letter determines the unknown parameters by fitting the BER approximation to a few BER values known in advance. The BER comparison with the exact results shows that the accuracy of the proposed low‐complexity approach is satisfactory for several constellation sizes of interest. This enables the possibility of BER self‐computation in low‐complexity devices that use orthogonal signals, like those used in the Internet of Things (IoT).